INTEGRASI PERTANIAN DAN PETERNAKAN DI DAYAH AL HUDA MALIKUSSALEH GAMPONG REULEUT TIMUR - Nasruddin Agani; Muhammad Nazaruddin; Khusrizal; Yusra; Jamidi (Politeknik Negeri Sriwijaya, 2022)
Dayah (Islamic Boarding School) Al Huda Malilkussaleh Gampong Reuleut Timu, Muara Batu District, North Aceh Regency is a traditional dayah. Having sufficient land to build dayah education facilities, a place for farming and animal husbandry. In order to increase their income and fulfill their daily needs, the dayah teacher conducts farming and goat/sheep farming. This business has been running for about two years and has experienced problems in terms of providing feed for their livestock. So far, the fulfillment of animal feed is obtained from plants or grass that grows wild/naturally and is often not available enough or to get it in remote locations. Based on this, in order to solve the problems it faces, it is necessary to carry out community service which aims to provide and increase its capacity in providing animal feed. This fulfillment is done through corn cultivation methods and training in the manufacture of fermented animal feed from agricultural waste either from corn, rice straw or other crops. This implementation forms the integration of agriculture and animal husbandry that benefits and benefits from both. This service produces outputs in the form of animal feed products, increasing the ability and skills of dayah teachers as farmers/breeders